CHALLENGE THE STEREOTYPES: ISLAM VOICES AS A FORM OF DECOLONIAL FEMINISM IN UZMA JALALUDDIN’S NOVEL AYESHA AT LAST - Akbar, Rifqi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
Halal Fiction is a sub-genre that seeks to represent Muslims in a way that reduces Islamophobia. Islamophobia often perpetuates grand narratives that marginalize women's identities, particularly in regions where the population is predominantly Muslim, such as the Middle East, Africa, South Asia, and Southeast Asia. A descriptive-qualitative approach is one methodological strategy within decolonialism, aimed at redefining heteropatriarchal Islamic principles. This approach can be informed by feminist decolonial theory, as proposed by Françoise Verges. The novel Ayesha at Last addresses inequality in marriage and Islamic paradigms through its characters Ayesha and Farzana. This portrayal challenges the perception of Islam as immoral, particularly among Muslim women. Farzana believes that Ayesha has become a moderate Muslim woman, eroding traditional Muslim values, which she deems unsuitable for her son Khalid to marry into. The research aims to challenge stereotypes of Muslim values, advocating for equality between men and women regardless of geopolitical and educational status. The findings reveal that through the character of Ayesha, who transitions from traditional to moderate Islam, the novel demonstrates that Islam is a religion that upholds equal values between men and women, without any inherent differences or harm to one another.